Instrument Radiometric Processing for Earh Observation Satellite Optical Payload - Tan, Ngo Duy; Tuyen, Bui Trong; Tuan, Pham Minh; Huy, Chu Xuan; Khiem, Dao Hong; Tien, Ngo Manh; Hong, Thai Thi Bich (Communications in Physics, 2019)
The radiometric calibration procedure, applied on VNREDSat-1 raw data shall correct and minimize the radiometric non-uniform gain and offset, occurred by the nature of the optical payload. The procedure is based on the radiometric model, built to transform the incoming radiance into camera output signal. Within this radiometric model, the radiometric parameters such as dark noise and pixel response non-uniformity shall be separated. The output signal of dark noise shall be measured by capturing image scene of the ocean at night. The output signal of pixel response non-uniformity shall be measured by capturing image scene of uniform radiance image scene such as the dessert or grass field. All the radiometric calibration parameter after calculated shall be saved into a calibration file, which is kept on the control station and image processing station.